Randomized Clinical Trial to Assess the Impact of the Broadly Neutralizing HIV-1 Monoclonal Antibody VRC01 on HIV-1 Persistence in Individuals on Effective ART. (20th October 2018) - Riddler, Sharon A; Zheng, Lu; Durand, Christine M; Ritz, Justin; Koup, Richard A; Ledgerwood, Julie; Bailer, Robert T; Koletar, Susan L; Eron, Joseph J; Keefer, Michael C; Macatangay, Bernard J C; Cyktor, Joshua C; et al.
Abstract: Background: Broadly neutralizing monoclonal antibodies (bnMAbs) may promote clearance of HIV-1-expressing cells through antibody-dependent cell-mediated cytotoxicity. We evaluated the effect of the CD4-binding site bnMAb, VRC01, on measures of HIV-1 persistence in chronically infected individuals. Methods: A5342 was a phase 1, randomized, double-blind, placebo-controlled, parallel-arm study. Participants on effective antiretroviral therapy (ART) were randomized to receive 2 infusions of VRC01 (40 mg/kg) at entry and week 3, and 2 infusions of placebo (saline) at weeks 6 and 9; or 2 infusions of placebo at entry and week 3, and 2 infusions of VRC01 at weeks 6 and 9. Results: Infusion of VRC01 was safe and well tolerated. The median fold-change in the cell-associated HIV-1 RNA/DNA ratio from baseline to week 6 was 1.12 and 0.83 for the VRC01 and placebo arms, respectively, with no significant difference between arms ( P = .16). There were no significant differences in the proportions with residual plasma viremia ≥1 copies/mL or in phorbol 12-myristate 13-acetate/ionomycin-induced virus production from CD4 + T cells between arms (both P > .05). Conclusions: In individuals with chronic HIV-1 infection on ART, VRC01 infusions were safe and well tolerated but did not affect plasma viremia, cellular HIV-1 RNA/DNA levels, or stimulated virus production from CD4 + T cells. ClinicalTrials.gov Identifier: NCT02411539